2021
DOI: 10.3390/nu13072183
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance and Accuracy of the MNA-SF against GLIM Criteria in Community-Dwelling Older Adults from Poland

Abstract: Up to 28% of elderly residents in Europe are at risk of malnutrition. As uniform diagnostic criteria for malnutrition have not been formulated, in autumn 2018, the Global Leadership Initiative on Malnutrition (GLIM) presented a consensus on its diagnosis. According to the consensus, the diagnosis of malnutrition requires a positive screening test result for the risk of malnutrition, and the presence of at least one etiologic and one phenotypic criterion. This study aimed to assess the diagnostic performance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Sanchez-Rodriguez et al [32] observed that more than half (60.4%) of community-dwelling older adults (mean age: 73.2 ± 6.05 years) with malnutrition according to the GLIM criteria had MNA-SF score of at least 12 [32]. Similarly, in our previous work [19] involving 273 community-dwelling elderly subjects (mean age: 72.1 ± 7.7 years), etiologic and phenotypic criteria for malnutrition were fulfilled in 103 individuals, of whom 41% (n = 42) had a negative screening result with the MNA-SF [19].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Sanchez-Rodriguez et al [32] observed that more than half (60.4%) of community-dwelling older adults (mean age: 73.2 ± 6.05 years) with malnutrition according to the GLIM criteria had MNA-SF score of at least 12 [32]. Similarly, in our previous work [19] involving 273 community-dwelling elderly subjects (mean age: 72.1 ± 7.7 years), etiologic and phenotypic criteria for malnutrition were fulfilled in 103 individuals, of whom 41% (n = 42) had a negative screening result with the MNA-SF [19].…”
Section: Discussionsupporting
confidence: 71%
“…These findings [19,32] question the value of MNA-SF as a screening tool for malnutrition in elderly subjects when the GLIM algorithm is used, in opposition to earlier reports [5,6]. Other screening tools have also been put under criticism.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The results of our previous work also demonstrated just fair diagnostics performance of the MNA-SF questionnaire as a screening tool in the GLIM criteria. Thus, we suggested using a clinical suspicion of malnutrition interchangeably with a screening tool in the first step of the GLIM algorithm [ 40 ].…”
Section: Discussionmentioning
confidence: 99%